Togetherness - Jayez, Jacques; Mari, Alda (Proceedings of Sinn und Bedeutung, 2019)
This paper investigates the notion of ‘togetherness’ expressed by adverbials like together in English or ensemble in French. We show that the natural division between the main uses of these adverbials is aspectual: whereas achievements impose no significant restrictions, non-achievements demand that the eventualities that are grouped ‘together’ be causally controlled or coordinated. In particular, contrary to what is frequently assumed in the literature, it is not sufficient that they occupy the same spatio-temporal location. This leads us to propose a new picture of togetherness, which accounts for the intuitions of ‘grouping’ (Lasersohn) or ‘integration’ (Moltmann) but puts them in a different perspective.